Characterization of Different Kinds of Silicon Dioxide and Their Application in Low-Temperature Adsorption Refining of Fragrant Rapeseed Oil - WANG Weijun, YANG Bo, LI Wenlin, MA Xuan, LIU Changsheng (Shipin Kexue, 2023)
Three kinds of silicon dioxide including S655, R92 and R40F were characterized, and their application in low-temperature adsorption refining of fragrant rapeseed oil was studied. The results showed that all three kinds of silicon dioxide had a loose porous structure, but the particle size distribution, specific surface area, pore volume and pore size were obviously different. After being treated with 1.0% silicon dioxide at 45 ℃ for 30 min, the dephosphorization rates of rapeseed oil by S655, R92 and R40F were 90.3%, 99.6% and 88.5%, the lightness increased by 49.9%, 52.5% and 53.9%, the redness decreased by 31.5%, 23.4% and 37.8%, the yellowness increased by 17.3%, 20.0% and 20.6%, respectively. Meanwhile, the retention rate of sterols (above 97.1%) was high, and there were no significant differences in deacidification rate, fatty acid composition or tocopherol retention rate among the three treatment groups. The highest retention rates of total phenol and canolol (98.1% and 99.4%) were found in the samples treated with R92. The contents of glucosinolate degradation products, pyrazines, aldehydes and ketones in fragrant rapeseed oil all increased significantly after refining with the three kinds of silicon dioxide.